Urban forest indicator assessment for nature-based solutions to connect biodiversity and people - Jinsuk Jeong; Chan-Ryul Park (Ecological Indicators)
Urban forests are essential for supporting ecosystem functions that benefit both city residents and urban biodiversity. This study assessed urban forests through three key indicators—availability, accessibility, and connectivity—to create balanced, nature-based solutions for sustainable urban forest management. Availability serves as a straightforward and comparable criterion that provides resources for both humans and biodiversity in urban areas. However, accessibility and connectivity indicators exhibit distinct and sometimes contradictory characteristics, emphasizing the complexity of balancing human access with ecological continuity. At the practical management scale of urban forests, walking-based accessibility and the Integral Index of Connectivity emerged as particularly strong contrasting indicators, offering valuable insights for tailoring management strategies to local needs. These findings indicate the need to harmonize urban forest policies to meet the needs of both residents and urban biodiversity, ensuring the long-term health and resilience of urban ecosystems.